Effects of Ionic Strength on the Uptake of Taurine and Glycine onto a Strongly Basic Anion-Exchange Resin - Feng Song; Zhong Li; Qibin Xia; Hongxia Xi; Zhenxia Zhao (Adsorption Science & Technology, 2006)
The effect of ionic strength on the competitive ion-exchange equilibria of taurine and glycine on the strong basic anion-exchange resin D290 has been studied. The adsorption isotherms of taurine and glycine onto D290 were measured and the distribution coefficients of taurine relative to glycine on the resin were calculated at different ionic strengths. The breakthrough curves and the elution peak profiles of taurine and glycine onto a fixed bed packed with D290 were determined. The effects of ionic strength on the breakthrough times of solutes through the fixed bed and the resolution of the taurine and glycine elution curves were discussed. The results obtained show that the amount of taurine taken up by the D290 resin was higher than that of glycine, and that the selectivity of D290 for taurine was larger than that for glycine. The higher the ionic strength of the solution, the lower the amount of taurine or glycine taken up by D290. With increasing solution ionic strength, the magnitude of the distribution coefficient of taurine relative to that of glycine decreased, as did the breakthrough times for glycine and taurine and the resolution of their elution curves.